Pengaruh Capital Expenditure Terhadap Respon Investor Pada Perusahaan Sektor Pertambangan Tahun 2014-2018 - Juan Hansel; Juniarti Juniarti (Business Accounting Review, 2020)
The purpose of this study is to determine whether Capital Expenditure has an effect on investor reponse. The method used collect data in this research is documentation technique, through data from Bloomberg in 2014-2018, then the data obtained is checked acording to the needs of research analysis so that the data obtained is reliable data. Management of activity data in this study using Gretl software, the results of this study indicate that Capital Expenditure has a positive effect on rejected CAR.